INTRASEASONAL OSCILLATIONS IN ASIA TO WESTERN PACIFIC REGION IN BOREAL SUMMER：CONTRASTIVE ANALYSIS FOR ACTIVE AND INACTIVE YEARS OF TROPICAL CYCLONES - 何洁琳 万齐林 管兆勇 林爱兰 王黎娟 (Journal of Tropical Meteorology, 2011)
Comparative analysis is carried out by using finite-domain power spectrum and lagged regression methods for the propagating characteristics and air-sea interaction processes of intraseasonal oscillations （ISOs） in the Asia to western Pacific （AWP） region during the boreal summer between the active and inactive tropical cyclone （TC） years from 1979 to 2004.The results show as follows.（1） There exist more significant eastward propagating characteristics of the ISO in the active TC years over the whole AWP region.The ISOs of convection propagate zonally with more eastward extension in the years with active tropical cyclone activities,during which the 20-60-day period is strengthened,western Pacific becomes an area with evident characteristics of the propagation that is closely related to TC activities.（2） The air-sea interaction processes are the same in both active and inactive TC years,and the energy exchanges between the air and the sea play a role in maintaining the northwestward propagation of ISOs.（3） The air-sea interaction is more intensive in the active TC years than in the inactive ones.It is particularly true for the latent heat release by condensation as the result of convection,which may be one of the reasons resulting in significant differences in characteristics of ISOs between the active and inactive TC years.